2017
DOI: 10.1177/1010428317695028
|View full text |Cite
|
Sign up to set email alerts
|

HR+HER2− breast cancers with growth factor receptor–mediated EMT have a poor prognosis and lapatinib downregulates EMT in MCF-7 cells

Abstract: Despite an overall good prognosis, a significant proportion of patients with hormone receptor positive human epidermal growth factor receptor 2 negative breast cancers develop distant metastases. The metastatic potential of epithelial cells is known to be regulated by tumor-stromal interaction and mediated by epithelial-to-mesenchymal transition. Hormone receptor positive human epidermal growth factor receptor 2 negative tumors were used to estimate markers of epithelialto-mesenchymal transition, and the lumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 52 publications
2
7
0
1
Order By: Relevance
“…Additionally, we found that ELK1 targets are overexpressed in CM-fated iPSCs, which is consistent with previous studies showing that knockdown of ELK1 in immortalized human bronchial epithelial cells, small airway epithelial cells, and luminal breast cancer cell line (MCF-7) is associated with increased EMT (Desai et al, 2017;Tatler et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we found that ELK1 targets are overexpressed in CM-fated iPSCs, which is consistent with previous studies showing that knockdown of ELK1 in immortalized human bronchial epithelial cells, small airway epithelial cells, and luminal breast cancer cell line (MCF-7) is associated with increased EMT (Desai et al, 2017;Tatler et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Circulating tumor cells (CTC) that show an EMT signature could form an early metastatic alert [69] or serve to detect minimal residual disease after therapy [70]. In an in vitro study on luminal breast cancer MCF-7 cell lines developing EMT expression induced by transcription factors, Lapitinib administration was shown to downregulate EMT expression [71]. Additionally, newer therapies may complement or supplement existing modalities improving patient outcome especially in poor-prognosis subsets of breast cancer.…”
Section: Future Directionsmentioning
confidence: 99%
“…Here, we used cell lines with different metastatic potentials; the MDA-MB-231 line is a highly invasive and metastatic triple-negative model, whereas MCF-7 is a luminal non-invasive breast cancer cell line model [20,21]. The expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal receptor (HER) in breast tumors plays a role in crucial cellular events, like chemoresistance and invasiveness [22]. In addition, MCF-7 presents wild-type p53 protein, while MDA-MB-231 harbors mutant p53 with loss-of-function which confers poor prognosis and contributes to the MDR phenotype observed in some breast cancers [23].…”
Section: Discussionmentioning
confidence: 99%